Fostering Critical Thinking Skills in Pre-Service Teachers: Examining Its Impact on Pedagogical Competence in Instructional Designs - Rahayu, Endang Mastuti (Journal of Applied Linguistics and English Education, 2025)
One of the core skills that helps aspiring teachers create learner-centered, reflective, and successful lessons is critical thinking. However, critical thinking is often assumed to develop implicitly in teacher preparation programs, leading to fragmented instructional design and limited pedagogical reasoning. With a focus on instructional design practice, this study aims to investigate how pre-service teachers' pedagogical competency was affected by the Development of critical thinking abilities. Fifteen students from PGRI Adi Buana University Surabaya's English Language Education Department, batch of 2022, who were enrolled in the instructional design course, participated in this study using a descriptive qualitative research methodology. Data were gathered through semi-structured interviews, reflective journals, classroom observation, and analysis of lesson plan documents. Learning objectives, instructional activities, and assessment procedures are more closely aligned, and pedagogical decision-making is more reflective when critical thinking skills are developed. These findings showed that essential skills of thinking Development enhance pedagogical competence. The capacity of student instructors to anticipate student needs, justify instructional decisions, and incorporate higher-order thinking exercises into their lesson plans has improved. This study concluded that, to enhance pedagogical competence and prepare future educators for challenging learning environments, critical thinking must be explicitly incorporated into the teacher education curriculum.